PENGARUH PENDIDIKAN KESEHATAN TERHADAP PENGETAHUAN DAN SIKAP REMAJA PUTRI USIA 18-24 TAHUN TENTANG PENTINGNYA TABLET FE DI WILAYAH KELURAHAN TLOGOMAS, LOWOKWARU - Alus, Katarina; Retnaningsih, Reny; Alfitri, Rosyidah (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Anemia occurs more often in women than men. The factor that causes anemia in adolescent girls is irregular menstrual cycles (Suparji, 2017). WHO states that globally the prevalence of anemia in women aged 15 years and over is 28%. The prevalence of anemia among children aged 5-12 in Indonesia is 26%, among women aged 13-18 it is 23%. The prevalence of anemia in adolescent girls in East Java in 2018 was included in the severe category, namely 42.1% (East Java Provincial Health Office, 2020). The research design used in this research was Pre-Experimental with One Group Pre-test and post-test design. The population used in this research was 30 young women. Samples were taken by total sampling technique. The number of respondents used in this study was 30 respondents. The results of univariate analysis of 30 respondents showed that most of them had knowledge about the importance of Fe tablets in the poor category, 22 respondents (73.3%) before the experiment (pre-test) and the majority had knowledge about the importance of Fe tablets in the sufficient category, 20 respondents (60%) after the experiment (post-test). All respondents had an attitude about the importance of Fe tablets in the poor category, 30 respondents (100%) before the experiment (pre-test) and almost all respondents had an attitude about the importance of Fe tablets in the good category, 28 respondents (100%) after experiment (post-test). There is an influence of health education on the knowledge of young women aged 18-24 years about the importance of Fe tablets in the Tlogomas Lowokwaru Village Area with a P value of 0.000. There is an influence of health education on the attitudes of young women aged 18-24 years about the importance of Fe tablets in the Tlogomas Lowokwaru Village Area with a P value of 0.000.